2010
DOI: 10.1016/j.bbrc.2010.10.091
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of tumorigenic circulating melanoma cells

Abstract: Circulating tumor cells (CTC) have been identified in several human malignancies, including malignant melanoma. However, whether melanoma CTC are tumorigenic and cause metastatic progression is currently unknown. Here we isolate for the first time viable tumorigenic melanoma CTC and demonstrate that this cell population is capable of metastasis formation in human-tomouse xenotransplantation experiments. The presence of CTC among peripheral blood mononuclear cells (PBMC) of murine recipients of subcutaneous (s.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 25 publications
(66 reference statements)
2
61
0
Order By: Relevance
“…Indeed, melanoma circulating tumor cells have recently been shown to contain an ABCB5 þ subpopulation, and the presence of circulating ABCB5 þ tumor cells was predictive of metastatic progression in tumor xenotransplantation models. 129 Migration and metastasis of melanoma cells may mimic a physiologic process, known as EMT, in which polarized, immotile epithelial cells lose cell-cell and cell-matrix connections and acquire the motile, migratory properties of mesenchymal cells. In states of malignancy, EMT confers metastatic and invasive properties to carcinomas, 130 and some studies have suggested that it is a major determinant of disease progression and metastasis in melanoma.…”
Section: How Primitive Melanoma Cells May Encourage 'Vasculogenic Mimmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, melanoma circulating tumor cells have recently been shown to contain an ABCB5 þ subpopulation, and the presence of circulating ABCB5 þ tumor cells was predictive of metastatic progression in tumor xenotransplantation models. 129 Migration and metastasis of melanoma cells may mimic a physiologic process, known as EMT, in which polarized, immotile epithelial cells lose cell-cell and cell-matrix connections and acquire the motile, migratory properties of mesenchymal cells. In states of malignancy, EMT confers metastatic and invasive properties to carcinomas, 130 and some studies have suggested that it is a major determinant of disease progression and metastasis in melanoma.…”
Section: How Primitive Melanoma Cells May Encourage 'Vasculogenic Mimmentioning
confidence: 99%
“…It has been hypothesized that cancer stem cells represent a pool of resistant cells in cancer patients. 99 In melanoma, cancer stem cells have been described as chemoresistant 30,43 and immunoevasive, 103 and have been associated with metastases 147 virulence-associated phenomenon of VM. 37,38,118,123 These protective properties for the melanoma stem cell translate into tumor aggressiveness directed against the patient.…”
Section: Translational Relevance Of Melanoma Stem Cellsmentioning
confidence: 99%
“…This has been demonstrated in xenotransplantation models, whereby CTCs were isolated from patients with melanomas. These CTCs were found to generate metastases in the models [77]. MET may establish the disseminated CSCs [4].…”
Section: Cancer Stem Cells Circulating Tumor Cells and Metastasismentioning
confidence: 99%
“…More specifically, highly tumorigenic melanoma stem/progenitor cells have been identified in situ and isolated from primary and secondary melanoma tumors, circulating melanoma cells and established melanoma cell lines [20,21,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] . Melanoma stem/progenitor cells may express different stem cell-like markers such as CD133, nestin, aldehyde dehydrogenase (ALDHhigh ), CD166, neural crest nerve growth factor receptor (CD271) and/or ATP-binding cassette (ABC) multidrug resistance transporters such as multidrug resistance-1 encoding P-glycoprotein (P-gp), ABCG2 and ABCB5.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma stem/progenitor cells may express different stem cell-like markers such as CD133, nestin, aldehyde dehydrogenase (ALDHhigh ), CD166, neural crest nerve growth factor receptor (CD271) and/or ATP-binding cassette (ABC) multidrug resistance transporters such as multidrug resistance-1 encoding P-glycoprotein (P-gp), ABCG2 and ABCB5. It has been shown that highly tumorigenic melanoma stem/progenitor cells can give arise to the total tumor cell mass in vivo with the phenotypic features resembling to original patient's melanomas and metastasize at distant sites [50][51][52][53][54][55][56][57][58]60,61,[63][64][65] . In this matter, we review the most recent advancements on the gene products that are often altered during melanoma initiation and progression to locally invasive and metastatic disease states and which may be exploited to develop novel multiplex biomarker detection methods for optimizing diagnosis and prognosis and multitargeted therapies for a more effective management of melanoma patients.…”
Section: Introductionmentioning
confidence: 99%